Playing distressed art: Adorno’s aesthetic theory in game design - Hanussek, Benjamin (Replay. The Polish Journal of Game Studies, 2022)
The discussion on games as (not) art has been raging for decades without reaching a consensus. It is argued here that the ontological status of games is irrelevant for the perception and development of aesthetic experiences in videogames. Instead, game design should be regarded as ripe to convey the experience of art according to established aesthetic theories. The essay presents Adorno’s aesthetic theory and highlights its reflections in the games Papers, Please and Observer. It then describes how they were synthesized into a critical gameplay experience in the author’s game Distressed. The latter may be regarded as an example of a method in game studies in which the aesthetic potential of games is explored by creation rather than analysis. Arguably, this reveals the importance of epistemological approaches towards games and art instead of the predominant ontological ones.